Human NK cells - Moretta, Lorenzo (Henry Stewart Talks, 2015)
NK cells and their contribution to innate & adaptive immunity, Triggering NK receptors and their cellular ligands, Effect of the tumor microenvironment on NK cell function, NK cells and haploidentical hematopeoitic stem cell therapy (HSCT) in high risk leukemias